Efficacy and Safety of Tamsulosin in the Medical Expulsion Therapy for Distal Ureteral Calculi: A Systematic Review and Meta-Analysis of Placebo-Controlled Trials - Tao, Rong-zhen; Qin, Zhi-qiang; Liu, Fa-de; Lv, Jian-lin (Urology Journal, 2019)
Purpose: Tamsulosin, a medical expulsive therapy (MET), was always recommended for patients with distal ureteral calculi less than 10 mm. The aim of the systematic review was to assess the efficacy and safety of tamsulosin in MET compared with placebo. Materials and Methods: A comprehensive search was conducted in the databases PubMed, EMBASE and Web of Science for relevant articles, covering all the literatures published until April 2018. All placebo controlled trails were identified in which patients were randomized to receive either tamsulosin or placebo for distal ureteral calculi. Results: A total of seven placebo controlled studies including 4135 patients met the inclusion criteria and were involved in the review. We found that tamsulosin was associated with a significantly higher expulsion rate (ESR) [odds ratio (OR) = 1.10, 95% confidence interval (CI) = 1.00-1.21] than placebo in patients with distal ureteral stones less than 7 mm. The ESR ranged from 67.0%-90.7%. But the significant difference was better seen in patients with distal ureteral stones less than 10 mm (OR = 1.11, 95% CI = 1.01-1.21). Even though tamsulosin has a higher incidence of retrograde ejaculation than placebo, no significant difference was observed in the incidence of other adverse events. Conclusion: The results of the current meta-analysis indicated that tamsulosin was superior to placebo in its efficacy for distal ureteral stones though retrograde ejaculation was worse with tamsulosin use. It should be a safe and effective medical expulsive therapy choice for distal ureteral stones when stone sizes are less than 10 mm.